Overexpression of β-carotene hydroxylase gene (CiBCH) enhances salt stress tolerance in Arabidopsis thaliana - Ying Sun; Ying Song; Shuaitong Zang; Ruiqing Zhang; Hongyao Li; Qiang Li; Liran Yue; Changle Liu; Miao He (Physiology and Molecular Biology of Plants, 2026)

Effects of Dietary Protein Sources on Vitellogenin of Female Largemouth Bass (Micropterus salmoides) - Yue Tan; Yang Xu; Li Jia; Youqin Kong; Zhili Ding; Changle Qi; Qiyou Xu (Fishes, 2026)
To investigate the effects of three alternative protein sources—Hermetia illucens larvae meal (HIM), Chlorella meal (CM) and stickwater meal (SWM)—on the vitellogenin in female largemouth bass (Micropterus salmoides), these protein sources were used to replace 0% (control group, FM; containing 40% fishmeal), 25% and 50% of the fishmeal in the diet. A total of seven isonitrogenous and isolipidic diets were formulated (FM, 25% HIM, 50% HIM, 25% CM, 50% CM, 25% SWM and 50% SWM). The healthy female fish with an initial body weight of 353.57 ± 28.12 g were fed the experimental diets for eight weeks. The results showed that the viscerosomatic index, gonadosomatic index and oocyte diameter of broodstock in the 50% HIM group were significantly higher than those in the FM group. The 50% HIM group showed the highest rate of stage IV oocytes and the lowest share of stage II oocytes. Hepatic vitellogenin (Vg) mRNA expression was significantly upregulated in the 50% HIM group, whereas ovarian mRNA expression of Vg and vitellogenin receptor (VgR) was significantly upregulated in the 25% SWM and 50% SWM groups. In conclusion, replacing 50% of dietary fishmeal with Hermetia illucens larvae meal can promote ovarian development in largemouth bass broodstock by increasing the gonadosomatic index and the expression of genes involved in vitellogenin synthesis.

Multiphysics modeling of synergistic microwave heating and nitrogen injection for methane hydrate recovery - Xiaowei Zhang; Yanlong Guan; Changle Yue; Zhigang Sun; Huiying Guo; Yuankai Zhang; Diansheng Wang; Yudou Wang (Fuel, 2026)

MOF-derived NiMoS hollow sphere for efficient hydrodesulfurization: Effects of composition and morphology of active phase of NiMoS catalysts - Dengwei Yan; Fengyue Sun; Yanwei Ju; Haoping Di; Changle Yue; Yanfei Chen; Chongzheng Xu; Yukun Lu (Fuel, 2025)

In-situ bond conversion strategy to construct Pt/1T-MoS2 heterojunctions by MOF-confinement for hydrogen evolution reaction in wide-pH-value water and seawater - Haoyuan Hao; Yukun Lu; Na Liu; Wenjing Bao; Fengyue Sun; Cong Zhang; Dengwei Yan; Changle Yue (Fuel, 2025)

Effects of Soybean Isoflavones on the Growth Performance and Lipid Metabolism of the Juvenile Chinese Mitten Crab Eriocheir sinensis - Mengyu Shi; Yisong He; Jiajun Zheng; Yang Xu; Yue Tan; Li Jia; Liqiao Chen; Jinyun Ye; Changle Qi (Fishes, 2024)
In order to study the effects of soybean isoflavones on the growth performance and lipid metabolism of juvenile Chinese mitten crabs, six experimental diets were formulated by gradient supplementation with 0%, 0.004% and 0.008% soybean isoflavones at different dietary lipid levels (10% and 15%). The groups were named as follows: NF-0 group (10% fat and 0% SIFs), NF-0.004 group (10% fat and 0.004% SIFs), NF-0.008 group (10% fat and 0.008% SIFs), HF-0 group (15% fat and 0% SIFs), HF-0.004 group (15% fat and 0.004% SIFs) and HF-0.008 group (15% fat and 0.008% SIFs). All crabs with an initial weight of 0.4 ± 0.03 g were fed for 8 weeks. The results showed that dietary supplementation with 0.004% or 0.008% SIFs significantly increased the weight gain and specific growth rate of crabs. Diets supplemented with 0.004% or 0.008% SIFs significantly reduced the content of non-esterified free fatty acids and triglycerides in the hepatopancreas of crabs at the 10% dietary lipid level. Dietary SIFs significantly decreased the relative mRNA expressions of elongase of very-long-chain fatty acids 6 (elovl6), triglyceride lipase (tgl), sterol regulatory element-binding protein 1 (srebp-1), carnitine palmitoyltransferase-1a (cpt-1a), fatty acid transporter protein 4 (fatp4), carnitine palmitoyltransferase-2 (cpt-2), Δ9 fatty acyl desaturase (Δ9 fad), carnitine palmitoyltransferase-1b (cpt-1b), fatty acid-binding protein 10 (fabp10) and microsomal triglyceride transfer protein (mttp) in the hepatopancreas of crabs. At the 15% dietary lipid level, 0.008% SIFs significantly increased the relative mRNA expressions of fatty acid-binding protein 3 (fabp3), carnitine acetyltransferase (caat), fatp4, fabp10, tgl, cpt-1a, cpt-1b and cpt-2 and significantly down-regulated the relative mRNA expressions of Δ9 fad and srebp-1. In conclusion, SIFs can improve the growth and utilization of a high-fat diet by inhibiting genes related to lipid synthesis and promoting lipid decomposition in juvenile Chinese mitten crabs.

Effects of Dietary Glutamate on the Growth Performance and Antioxidant Capacity of Juvenile Chinese Mitten Crab (Eriocheir sinensis) - Jiajun Zheng; Yisong He; Mengyu Shi; Li Jia; Yang Xu; Yue Tan; Changle Qi; Jinyun Ye (Fishes, 2024)
In order to explore the effects of glutamate on the growth performance, antioxidant capacity and protein metabolism of juvenile Chinese mitten crab, 0%, 1% and 2% glutamate were supplemented to low protein (30%) and normal protein (35%) diets, respectively. There were 5 parallel tanks in each treatment, and the feeding duration was 8 weeks. The results showed that dietary glutamate did not significantly affect the weight gain of Chinese mitten crab. Diets supplemented with 2% glutamate significantly decreased the crude protein of crabs. The T-AOC of crabs fed the 30% protein diets was significantly lower than crabs fed the 35% protein diets. At 30% protein level, the superoxide dismutase (SOD) activity significantly increased with the increase in glutamate content. Dietary glutamate significantly down-regulated the relative expressions of mTOR, PI3K, S6K1 and 4EBP at 35% protein level. In conclusion, dietary glutamate cannot significantly increase the growth of Chinese mitten crab, but it can improve the antioxidant capacity in Chinese mitten crab under low protein conditions.

Construction of ultrafine and highly dispersed RuSe2 on WOx by “atom-to-cluster” strategy for efficient hydrogen evolution reaction - Fengyue Sun; Wenjing Bao; Chao Feng; Jiahui Bi; Changle Yue; Cong Zhang; Na Liu; Haoyuan Hao; Yukun Lu (Fuel, 2024)

The organic–inorganic dual anchoring strategy based on organic chelators and lacunary polyoxometalates for the preparation of efficient CoWS hydrodesulfurization catalysts - Wenjing Bao; Cong Zhang; Dengwei Yan; Fengyue Sun; Changle Yue; Chongze Wang; Yukun Lu (Fuel, 2024)

High phase purity of stable 1T-phase Co-doped WS2 for full pH hydrogen evolution reaction in water and seawater - Changle Yue; Fengyue Sun; Na Liu; Yang Liu; Wenjing Bao; Xiaowei Zhang; Cong Zhang; Shuyan Ma; Yan Zhou; Chao Feng; Yukun Lu (Fuel, 2024)

Superhydrophilic molybdenum phosphide quantum dots on porous carbon matrix for boosting hydrogen evolution reaction - Yang Liu; Changle Yue; Fengyue Sun; Wenjing Bao; Lulu Chen; Zonish Zeb; Chongze Wang; Shuyan Ma; Cong Zhang; Daofeng Sun; Yuan Pan; Yichao Huang; et al. (Chemical Engineering Journal, 2023)

First report of tomato spotted wilt virus (TSWV) infecting Panax notoginseng (Burk.) F.H. Chen in China - Changle Ma; Xiaofang Zhang; Yue Cui; Mingfu Zhao; Zhongkai Zhang; Lihua Zhao (Journal of Plant Pathology, 2022)